RISING DANGER OF AIR CONDITIONERS: A NECESSITY OR A LUXURY? - Uroš Breskvar (Agora International Journal of Economical Sciences, 2025)
Air conditioners have become an indispensable part of modern life, providing a comfortable indoor climate, especially during the hot summer months. However, their use comes with environmental consequences. The increased electricity consumption required to power air conditioners significantly contributes to greenhouse gas emissions and further exacerbates climate change. This research focuses on the use of air conditioners and addresses the question of whether they are used rationally. Methods for reducing air conditioner usage and promoting their proper use are presented. The study analyzes the relationship between air conditioner electricity consumption, GDP, and temperature, highlighting the significant correlation between air conditioner usage and economic prosperity rather than climate conditions. A discussion on policy measures, energy efficiency improvements, and behavioral adaptations is also included.